Broadening the wheat gene pool for stem rust resistance through genomic-assisted introgressions from Aegilops tauschii - Olson, Eric Leonard (Kansas State University, 2012)
The diploid D genome species, Aegilops tauschii Coss. (2n=2x=14,DD) has provided numerous genes for resistance to diseases and insect pests that attack bread wheat (Triticum aestivum L. (2n=6x=42, AABBDD). Wheat production is currently threatened by broadly virulent races of the ‘Ug99’ lineage of wheat stem rust caused by the fungus, Puccinia graminis f.sp. tritici Pers. & Eriks. Screening of a large set of Ae. tauschii germplasm for resistance to TTKSK (Ug99) identified potentially novel sources of resistance. To expedite utilization of TTKSK resistance from Ae. tauschii, a direct hybridization approach was established that integrates gene transfer, mapping and introgression into one process. Direct crossing of Ae. tauschii accessions with an elite wheat breeding was used to initiate transfer of resistance. Genetic mapping of resistance was accomplished during gene transfer through development of BC[subscript]2 mapping populations. Bulked segregant analysis of BC[subscript]2F[subscript]1 genotypes at 70 SSR loci across the D genome identified the chromosome locations of stem rust resistance genes and facilitated genetic mapping. Using this approach, TTKSK resistance from CDL4424 and TA1662 was mapped on chromosome arm 1DS flanked distally by Xwmc432 and proximally by Xwmc222 at 4.4 cM, TA10187 on 6DS linked to Xcfd49 at 1.9 cM and TA10171 on 7DS linked Xwmc827 at 0.9 cM. TTKSK resistance from additional Ae. tauschii accessions CDL4366, TA1615, TA1642, TA1693 and TA1718 has been recovered in segregating populations but await mapping. Altogether, TTKSK resistance from eight Ae. tauschii accessions has been introgressed to a hard winter wheat genetic background. Three new stem resistance genes have been tagged with molecular markers for marker assisted breeding and will provide valuable material for stem rust resistance breeding and gene pyramids for effective control of stem rust.
Keywords: Wheat; Aegilops tauschii; Stem rust; Introgression; Genetics (0369); Plant Pathology (0480)